2021
DOI: 10.3390/ijms22147555
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Cerebrovascular Implications of Growth Restriction: Mechanisms and Potential Treatments

Abstract: Fetal growth restriction (FGR) is a common complication of pregnancy, resulting in a fetus that fails to reach its genetically determined growth potential. Whilst the fetal cardiovascular response to acute hypoxia is well established, the fetal defence to chronic hypoxia is not well understood due to experiment constraints. Growth restriction results primarily from reduced oxygen and nutrient supply to the developing fetus, resulting in chronic hypoxia. The fetus adapts to chronic hypoxia by redistributing car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…1 Hypoxic stress in pregnancy is one of the most common conditions and occurs in various scenarios such as high-altitude pregnancy, maternal smoking, pulmonary diseases, preeclampsia, placental insufficiency, and others. 2,3 Antenatal maternal hypoxia has been shown to cause altered cardiac growth and neonatal vascular function, 4,5 pulmonary arterial dysfunction 6 and fetal growth restriction. 7 Fetal growth restriction or intrauterine growth retardation (IUGR) is one of the major complications of pregnancy and is one of the main leading causes of perinatal death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Hypoxic stress in pregnancy is one of the most common conditions and occurs in various scenarios such as high-altitude pregnancy, maternal smoking, pulmonary diseases, preeclampsia, placental insufficiency, and others. 2,3 Antenatal maternal hypoxia has been shown to cause altered cardiac growth and neonatal vascular function, 4,5 pulmonary arterial dysfunction 6 and fetal growth restriction. 7 Fetal growth restriction or intrauterine growth retardation (IUGR) is one of the major complications of pregnancy and is one of the main leading causes of perinatal death.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition to the abnormal organic growth of the fetus, it can also induce long-term diseases including respiratory diseases (e.g. bronchopulmonary dysplasia), 6 cardiovascular diseases, 5 and metabolic syndrome. 12,13 The liver is the major organ related to the general body metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…However, the present systematic review found that none of the studies focused on the relationship between abnormal placenta and fetal anomaly. Our study revealed that circumvallate placenta was associated with increased rate of FGR (OR 3.53, 95%CI 1.63–7.62), and FGR has been correlated with adverse effects on neurological [ 74 , 75 , 76 ] and cardiovascular development [ 77 , 78 ] of the fetus depending on its severity. Therefore, circumvallate placenta can potentially be associated with adverse effects on neurological and cardiovascular development.…”
Section: Discussionmentioning
confidence: 73%
“…The relationship between alterations in intestinal perfusion and oxygenation after fetal hypoxia and the development of feeding intolerance and NEC has been examined in several studies. It is known that the fetus responds to hypoxia by redistributing blood flow to essential vascular beds, a process known as brain sparing [25].…”
Section: Discussionmentioning
confidence: 99%